2022
DOI: 10.1186/s13036-022-00300-0
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating immersive learning into biomedical engineering laboratories using virtual reality

Abstract: Background The Covid-19 pandemic caused a sudden shift towards remote learning, moving classes to online formats. Not exempt from this switch, laboratory courses traditionally taught in-person were also moved to remote methods, costing students the opportunity to learn these skills hands-on. In order for instructors to provide course materials effectively and engagingly, non-traditional methods should be explored. Virtual reality (VR) has become more accessible in recent years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
0
22
1
Order By: Relevance
“…The Table S11 in Supporting Information 1 provides access to all these metrics. Among the co-occurrences between keywords from different groups, after VR-Simulation (21) and VReducation (17) 91 and a VR electronics engineering lab. 74 Additionally, examples of publications where VR and Training were cited together include experiments with a VR civil engineering Lab, 92 a VR clinical Lab, 93 and a VR Automotive Lab.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Table S11 in Supporting Information 1 provides access to all these metrics. Among the co-occurrences between keywords from different groups, after VR-Simulation (21) and VReducation (17) 91 and a VR electronics engineering lab. 74 Additionally, examples of publications where VR and Training were cited together include experiments with a VR civil engineering Lab, 92 a VR clinical Lab, 93 and a VR Automotive Lab.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Among the co-occurrences between keywords from different groups, after VR-Simulation (21) and VR-education (17), the highest are VR and Engineering education (technology-target audience, cited together in 12 articles), VR and Training (technology-purpose, cited together in 7 articles), and Computer-Based Learning and Undergraduate education (purpose-target audience, cited together in 7 articles). Examples of VR and Engineering education publications include experiments with a VR biomedical engineering lab and a VR electronics engineering lab . Additionally, examples of publications where VR and Training were cited together include experiments with a VR civil engineering Lab, a VR clinical Lab, and a VR Automotive Lab .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous global studies have demonstrated that AR or VR systems and environments accelerate the acquisition of knowledge and skills by students more than any other instructional method (Wilkerson et al, 2022;Mohammadyari and Singh, 2015). Alike any other emerging technologies, the scholars wish to investigate the future prospects and potentials of immersive technology like AR and VR in mounting virtual education.…”
Section: Objective and Research Questionsmentioning
confidence: 99%
“…Traditional Case-Based Learning (CBL) is a proactive, problem-oriented teaching method that integrates real-life scenarios into the educational process. However, the outbreak of Covid-19 led to a shift towards online formats, and traditionally face-toface laboratory courses were also moved to remote methods [13]. In recent years, as VR has become increasingly popular, it has started to be applied in conjunction with CBL in the eld of medical education, providing students with speci c training scenarios to facilitate the transformation of theoretical knowledge into clinical practice experience [14].…”
Section: Introductionmentioning
confidence: 99%